La Loi constitutionnelle de 1982. Droit des autochtones - O’Reilly, James (Les Cahiers de droit, 1984)
This article deals with the rights of the Aboriginal Peoples of Canada recently recognized in the Constitution Act, 1982. It provides a brief analysis of the nature and scope of these rights and their historical context by reference to some of the principal cases on Indian title. There is a short treatment of section 91(24) of the Constitution Act, 1867, and finally a summary of the 1983 Constitutional Accord on Aboriginal Rights and the amendments to the Constitution of Canada contemplated by the Accord.